Proceedings of the ACL 2003 Workshop on Multiword Expressions Analysis, Acquisition and Treatment - 2003
DOI: 10.3115/1119282.1119294
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model of multiword expression decomposability

Abstract: This paper presents a constructioninspecific model of multiword expression decomposability based on latent semantic analysis. We use latent semantic analysis to determine the similarity between a multiword expression and its constituent words, and claim that higher similarities indicate greater decomposability. We test the model over English noun-noun compounds and verb-particles, and evaluate its correlation with similarities and hyponymy values in WordNet. Based on mean hyponymy over partitions of data ranke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 15 publications
0
98
0
4
Order By: Relevance
“…Previous studies determine compositionality by looking at the degree of distributional similarity between an expression and its component words (e.g., McCarthy et al, 2003;Bannard et al, 2003;Baldwin et al, 2003). Because light verbs are highly polysemous and frequently used in LVCs, such an approach is not appropriate for determining their contribution to the semantics of an expression.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Previous studies determine compositionality by looking at the degree of distributional similarity between an expression and its component words (e.g., McCarthy et al, 2003;Bannard et al, 2003;Baldwin et al, 2003). Because light verbs are highly polysemous and frequently used in LVCs, such an approach is not appropriate for determining their contribution to the semantics of an expression.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In many later works distributional models were used. Baldwin et al (2003) showed that LSA-based similarity between the multiword expression and each of its components is indicative for compositionality. Katz and Giesbrecht (2006) compared the actual phrase vector to the estimated compositional meaning vector calculated as a sum of the meaning vectors of the 772 parts.…”
Section: Existing Workmentioning
confidence: 99%
“…Several researchers have used latent semantic analysis (LSA) to distinguish between compositional and non-compositional preferences of expressions [17,18]. They show that compositional MWEs are generally more likely similar to their constituents than other non-compositional MWEs.…”
Section: Mwe Identificationmentioning
confidence: 99%